(untitled) (American Journal of Islam and Society, 2000)
This is a study of warfare fought in the name of God by Jews, Christians, and Muslims from biblical until modem times. The book is impressive in its scope and in the wide range of authorities consulted; the author has gone out of his way to be neutral and impartial. In his introduction, for example, Partner recognizes that "less than half a century ago, unconscious of their own arrogance and inaccuracy. Westerners used to write confidently about something they called the Arab mind" (p. xix). The book’s critical apparatus is nearly perfect: there is a glossary, a chronological table, and an index; and, in addition to a short bibliography with the notes to each chapter, there is a brief reading list on different topics. This means that students will find the book easy to use. Having said this, readers should be warned that, like most academic research, the general tone is dogmatically secular and cynical about spiritual motives. Although the author criticizes the prejudices of earlier historians, he himself speaks of Islam as "a program of conquest" and states that "Muslims set themselves almost from the outset the task of Islamizing the whole world by force of arms" (p. 38). Despite his remarks on the greater jihad, referring to the inner spiritual struggle against evil, there is little recognition of Islam as a spiritual message; he says that Muhammad ’’came to warn, perhaps also to conquer" (p. 42). Indeed, the striving denoted by the verb jahada is primarily spiritual or moral as in the admonition to the Prophet: "Strive hard against the deniers of the truth and the hypocrites" (9:73). Other passages indicate that the Qur’an itself is the instrument with which believers must strive against unbelievers (25:52; 66:9). As Seyyed Hossein Nasr says, concerning the concept of jihad, "Its translation into ’holy war,’ combined with the erroneous notion of Islam prevalent in the West as the ’religion of the sword,’ has helped to eclipse its inner and spiritual significance."1 All external forms of struggle, such as fighting ignorance and injustice, are incomplete without the inner struggle, and the result of that struggle will be peace and love: "Repel evil with that which is better. Then he between whom and thee there was enmity will become as though he had always been a bosom friend" (41:34) ...